PHYSICAL AND CHEMICAL CHARACTERIZATION OF WASTED TILES AS COATING MATERIALS FOR PAVEMENT SURFACE TEMPERATURE REDUCTION (Malaysian Journal of Civil Engineering, 2018)
Urban heat island (UHI) is the phenomenon that temperatures in urban area reach a relatively higher value than its surroundings areas due to urbanisation. Pavement is one of the urban fabrics that contribute to UHI, due to its ability to absorb high amount of heat from solar radiation. In the tile production process, cracked or broken tile bodies are not accepted as commercial products and they are too impure to be reused and is usually discarded as unsold waste. This scenario could possibly lead to environmental problems. This study focuses on three types of wasted tiles (Full Body Porcelain, Monoporosa, Glazed Porcelain) from a chosen tile industrial factory, as coating materials for pavement surface. The main purpose of this study is to obtain specific information regarding the significance characterization of three types of wasted tiles as coating materials on pavement surface. The title characterization showed that Full Body Porcelain contains the highest bulk density value of 1366.699 kg/m3 and highest particle density of 2580 kg/m3 , whereas Monoporosa has the highest porosity value of (56.8%) and Monoporosa posses the highest amount of void content (56.85%) between the aggregate particles. The X-Ray Fluorescence study shows that Full Body Porcelain contains the highest amount of SiOâ‚‚ (66.50 wt%), when compared to other two wasted tiles used during this study. As a conclusion these three types of wasted tiles have the potential and promising UHI mitigation benefits to be considered as coating materials for the pavement surface.